Patient Acceptance of Educational Voice Messages: A Review of Controlled Clinical Studies - Krishna, S.; Balas, E. A.; Boren, S. A.; Maglaveras, N. (Methods of Information in Medicine, 2002)
Objectives: The objective of this study was to evaluate controlled evidence on the impact of automated computer-based telephone messaging technology upon health outcomes, cost savings and acceptance by patients, caregivers and care providers.Methods: Systematic searches of electronic databases were conducted to find controlled clinical studies of automated phone messaging used in patient care. Studies were selected based on the three criteria: 1) randomized controlled trials or controlled trials; 2) patients receiving health care related education, information, advice or reminder for a specific action to be taken in their home setting; and 3) use of automated computer-based phone technology to deliver the messages. Information abstracted from studies included information about the institution, persons targeted, intervention and its effect on health outcomes, costs and acceptance by patients and caregivers.Results: A total of nineteen studies were identified for review. Sixteen studies were randomized controlled trials and three were controlled studies with no randomization. Studies were placed in two categories, preventive care education and chronic care studies. Preventive care education studies covered childhood immunizations, medication compliance, influenza vaccinations, tuberculosis and health prevention activities and chronic care studies were related to cholesterol, diabetes, hyper-tension and congestive heart failure. More than 80% of studies showed significant impact upon measurable health outcomes.Conclusions: Controlled evidence substantiates the efficacy of automated telephone communication in improving the quality of care. Educational voice messages are acceptable to patients and represent an important opportunity to enhance telemedicine and telehealth applications.
Keywords: Voice mail; automated messaging systems; patient education; telephone; telehealth